Baby Blues Syndrome in Postpartum Mothers and Islamic Perspective: A Qualitative Study in Gowa, Indonesia - Risnah, Risnah; Syisnawati, Syisnawati; Nurfadilah, Siti Namirah (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Baby blues syndrome or mild depression tends to be experienced by mothers in the first week after giving birth and can have an effect on the physiological condition of the mother and the child's development. This study aims to describe in more depth the experience of baby blues syndrome in postpartum mothers in the work area of the Samata Health Center, Gowa Regency, so that they know what are the causal factors and what symptoms are experienced by postpartum mothers with baby blues syndrome. Using qualitative research methods with a phenomenological approach. The sampling technique uses purposive sampling techniques and data analysis techniques according to Colaizzi. There are three informants and the results of this study have been arranged into several themes, namely; feelings, behavior and thoughts of mothers who experience baby blues syndrome, causes of baby blues syndrome in postpartum mothers, and psychosocial needs and spirituality of postpartum mothers in the letting go phase. The conclusion from this study is that social support is one of the dominant factors that trigger postpartum mothers to experience baby blues syndrome. The results of this study prove the view of the Qur'an that women are creatures that are not strong enough physiologically so that it is necessary to pay attention during pregnancy because this period is considered to cause increased weakness.